The military ordinariate and the personal ordinariate for former anglicans - similarities and differences - Dohnalik, Jan (Prawo Kanoniczne, 2020)
This study has been inspired by the intuition that the concept of personal ordinariate can be applied to various situations in the Church and seems to be very promising for the pastoral care in many exceptional situations. In fact, this juridical structure laid base for the pastoral care for the military and later was used to offer former Anglicans the possibility of entering full communion with the Catholic Church without losing their own customs and traditions. The article is divided into three parts. The first outlines the development of the concept of legal personal structures in the 20th century, especially from the 2nd Vatican Council. In the second part there are going to be presented major elements of the Military Ordinariate that were to be later used in the personal ordinariate for the former Anglicans. In the third part one will find key differences and new legal solutions designed exclusively for the personal ordinariate for those coming from Anglicanism. The study shows the significance of the juridical structures of personal ordinariate that in the future can be applied to another new pastoral needs in the changing world.